A histological study of the seminal vesicle of the armoured catfish Corydoras aeneus - Franceschini-Vicentini, I. B.; Papa, L. P.; Bombonato, Maria Terezinha Siqueira [UNESP]; Vicentini, Carlos Alberto [UNESP]; Ribeiro, K.; Orsi, A. M. (Blackwell Publishing, 2007)
Most species of Corydoras exhibited a reproductive behaviour called 'T-position', and exhibited an accessory gland in the male genital tract, called the seminal vesicle. It appeared that both the structure and the composition of the fluid varied considerably between the species investigated. Consequently, different opinions were proposed regarding the possible role of seminal vesicle on this particular reproductive behaviour. Male adults of Corydoras aeneus were collected, anaesthetized, and samples of seminal vesicle were fixed in Bouin's solution. The sections were stained with haematoxylin-eosin and periodic acid Schiff. The seminal vesicle showed a system of anastomosed secretory tubules, forming a vesicular collective network, which gave rise to the vesicular ducts. The latter fused with the testicular efferent ducts and formed the spermatic ducts. Considering this fusion, when the sperm cells reached the spermatic ducts, the fluid produced at the seminal vesicle covered them. Histochemical studies evidenced the presence of neutral and acid glycosaminoglycans in the seminal fluid. Considering the reproductive behaviour of C. aeneus, it is believed that the protection associated with the immobilization of the sperm cells assures the sperm integrity during the passage through female's intestine until fertilization.